ER-mediated control for abundance, quality, and signaling of transmembrane immune receptors in plants - Tintor, Nico; Saijo, Yusuke (Frontiers in Plant Science, 2014)
Plants recognize a wide range of microbes with cell-surface and intracellular immune receptors. Transmembrane pattern recognition receptors (PRRs) initiate immune responses upon recognition of cognate ligands characteristic of microbes or aberrant cellular states, designated microbe-associated molecular patterns (MAMPs) or danger-associated molecular patterns (DAMPs), respectively. Pattern-triggered immunity (PTI) provides a first line of defense that restricts the invasion and propagation of both adapted and non-adapted pathogens. Receptor kinases (RKs) and receptor-like proteins (RLPs) with an extracellular leucine-rich repeat (LRR) or lysine-motif (LysM) domain are extensively used as PRRs. The correct folding of the extracellular domain of these receptors is under quality control (QC) in the endoplasmic reticulum (ER), which thus provides a critical step in plant immunity. Genetic and structural insight suggests that ERQC regulates not only the abundance and quality of transmembrane receptors but also affects signal sorting between multi-branched pathways downstream of the receptor. However, ERQC dysfunction can also positively stimulate plant immunity, possibly through cell death and DAMP signaling pathways.